Pengaruh Profitabilitas, Likuiditas, Solvabilitas dan Aktivitas terhadap Nilai Perusahaan - Ni Made Mirayanti; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2023)
TThis study aims to determine the effect of Profitability, Liquidity, Solvency and Activity on Firm Value in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in the 2016-2020 Period. This research is a type of comparative causal research. The population of this research is the Food and Beverage Sector companies that are listed on the Indonesia Stock Exchange in the 2016-2020 period, as many as 14 companies. Based on the sampling technique with purposive sampling obtained as many as 70 samples from 14 companies. The data collection technique uses secondary data from financial reports published on www.idx.co.id. The analytical technique used in this research is Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing. The results of the study indicate that profitability has a positive and significant effect on the Firm Value variable. Liquidity has a negative and insignificant effect on the Firm Value variable. Solvency has a negative and insignificant effect on the Firm Value variable. Activity has a negative and insignificant effect on the Firm Value variable.